Chemosensitization of Therapy Resistant Tumors: Targeting Multiple Cell Signaling Pathways by Lupeol, A Pentacyclic Triterpene - Maurya, Santosh K.; Shadab, G.G.H.A.; Siddique, Hifzur R. (Current Pharmaceutical Design, 2020)
Background: The resistance of cancer cells to different therapies is one of the major stumbling blocks for successful cancer treatment. Various natural and pharmaceuticals drugs are unable to control drug-resistance cancer cell's growth. Also, chemotherapy and radiotherapy have several side effects and cannot apply to the patient in excess. In this context, chemosensitization to the therapy-resistant cells by non-toxic phytochemicals could be an excellent alternative to combat therapy-resistant cancers. Objective: To review the currently available literature on chemosensitization of therapy resistance cancers by Lupeol for clinically approved drugs through targeting different cell signaling pathways. Methods: We reviewed relevant published articles in PubMed and other search engines from 1999 to 2019 to write this manuscript. The key words used for the search were “Lupeol and Cancer”, “Lupeol and Chemosensitization”, “Lupeol and Cell Signaling Pathways”, “Cancer Stem Cells and Lupeol” etc. The published results on the chemosensitization of Lupeol were compared and discussed. Results: Lupeol chemosensitizes drug-resistant cancer cells for clinically approved drugs. Lupeol alone or in combination with approved drugs inhibits inflammation in different cancer cells through modulation of expression of IL-6, TNF-α, and IFN-γ. Lupeol, through altering the expression levels of BCL-2, BAX, Survivin, FAS, Caspases, and PI3K-AKT-mTOR signaling pathway, significantly induce cell deaths among therapy-resistant cells. Lupeol also modulates the molecules involved in cell cycle regulation such as Cyclins, CDKs, P53, P21, and PCNA in different cancer types. Conclusion: Lupeol chemosensitizes the therapy-resistant cancer cells for the treatment of various clinically approved drugs via modulating different signaling pathways responsible for chemoresistance cancer. Thus, Lupeol might be used as an adjuvant molecule along with clinically approved drugs to reduce the toxicity and increase the effectiveness.
Keywords: cancer signaling pathways